Farmers' Perceptions of the Farmer's Card Program in the Distribution of Subsidized Fertilizer (Jurnal Sosial Ekonomi Pertanian, 2024)
In order to support Indonesian agriculture, the Indonesian Government through the Ministry of Agriculture issued the Farmer Card Program. The Tani Card is a debit card issued by banks as a transaction tool for the redemption of subsidized fertilizer at designated official kiosks. The farmer's card program aims to ensure that the distribution of subsidized fertilizer is right on target and facilitates supervision that is directly integrated with SIMPI. This research aims to find out how farmers perceive the use of farmer cards in distributing subsidized fertilizer. The research period was carried out from August to September 2023. This type of research is qualitative descriptive research with a survey method. The research respondents were selected purposively, namely 48 farmers who had received farmer cards for the distribution of subsidized fertilizer. qualitative descriptive data analysis and using a Likert scale. From the research results, it can be concluded that farmers' perceptions of the farmer's card program in distributing subsidized fertilizer as a whole are in the good category with an index of 77.08% or an average of 3.85, then farmers' perceptions of the procedure for obtaining farmer's cards are in the quite good category with an index of 58 .3% or an average of 2.91, then the farmer's perception of the ease of using the farmer's card is in the good category with an index of 65% or an average of 3.25. Furthermore, the farmer's perception of the use of the farmer's card is in the good category with an index of 64.16% or the average -average 3.2.  This shows that the farmer's card program in the distribution of subsidized fertilizer in the Sijunjung sub-district has received quite a good perception from the community, even though there are still obstacles experienced by farmers in this farmer's card program in the field
Keywords: farmer perceptions; farmer cards; subsidized fertilizer